Challenges and approaches for production of a healthy and functional mayonnaise sauce. Issue 8 (18th July 2019) - Mirzanajafi-Zanjani, Mina; Yousefi, Mohammad; Ehsani, Ali
Abstract: Mayonnaise is a semisolid oil‐in‐water (O/W) emulsion which is made through the careful blending of oil, vinegar, egg yolk, and spices (especially mustard). In addition, mayonnaise traditionally contains 70%–80% oil, and egg yolk is a key ingredient contributing to its stability. Despite concerns about high cholesterol level in egg yolk, it is yet the most widely utilized emulsifying agent owing to its high emulsifying capacity. Today, the public knowledge about diet and health has been incremented, compelling the people to consume foodstuffs containing functional features. Thus, consumers, aware of the considerable influence of the diet on their health, demand nutritious and healthier food. Mayonnaise is usually cited by health‐related issues due to its high cholesterol and fat content. Many researchers have tried to replace fat, as well as egg yolk completely or partially; however, low‐fat mayonnaises require extra ingredients to keep the stability. In other words, each ingredient plays a specific role in textural and oxidative stability, and using alternative emulsifiers and fat replacers may affect the sensorial, textural, and antioxidant features of mayonnaise. Furthermore, mayonnaise, like other high‐fat foodstuffs, is vulnerable to auto‐oxidation. In addition to using fat replacers, mayonnaise is accompanied with bioactive ingredients to produce a healthy system. Therefore in this review, we gathered a quick summary of the ideas, including lowering the cholesterol and fat and using natural antioxidants, prebiotics, and probiotics in order to produce a healthy and functional mayonnaise sauce. Abstract : The main aim of the study is the expression of functional mayonnaise properties as well as the role of its different ingredients.